PERAN PRAMUWISATA DALAM PROMOSI KEPARIWISATAAN DI BALI - Bagus Satya Wira, Sang Nyoman; Pujaastawa, Ida Bagus Gde; Suryawardani, I Gusti Ayu Oka (Jurnal Master Pariwisata (JUMPA), 2019)
Tourism promotion is becoming the most important factor for the success of any destination. Every destination is applying the strategy based on its resources. For Balinese tourism, which is enriched by its cultural aspects, the role of tourist guide is still necessarily required. The essence of tourist guiding somehow is rarely recognised as promotional tool that should have been very possible to be focused on. Therefore, this study is aimed to discover the role of tourist guide as indirect promoter for the Balinese tourism. In order to accomplish that objective, examination was laid on Balinese promotion system, expectation of stakeholders/users, and tourist’s perception toward the roles of tourist guide. Based on the findings, the author has proposed a concept regarding the utilization of tourist guiding as word-of-mouth promotion strategy for the importance of Balinese tourism. Its composition consists of tourist guide as the promoter; actual tourist as the channel; and potential tourist as the target. Keywords : tourist guide, informal role, tourism promotion, word-of-mouth